2000
DOI: 10.2741/black
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-mediated regulation of the cell cycle

Abstract: Members of the protein kinase C (PKC) family of signal transduction molecules have been widely implicated in regulation of cell growth/cell cycle progression and differentiation. Increasing evidence from studies using in vitro and in vivo systems points to PKC as a key regulator of critical cell cycle transitions, including cell cycle entry and exit and the G 1 and G 2 checkpoints. PKC-mediated control of these transitions can be negative or positive, depending on the timing of PKC activation during the cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 130 publications
2
34
0
1
Order By: Relevance
“…Not surprisingly, studies from several laboratories highlight a role for PKCε in cell cycle control, specifically in G1 to S progression [165167]. In addition, PKCε promotes survival in many cell types [6, 168170].…”
Section: Pkcε: An Oncogenic and Metastatic Kinasementioning
confidence: 99%
“…Not surprisingly, studies from several laboratories highlight a role for PKCε in cell cycle control, specifically in G1 to S progression [165167]. In addition, PKCε promotes survival in many cell types [6, 168170].…”
Section: Pkcε: An Oncogenic and Metastatic Kinasementioning
confidence: 99%
“…PKC α is antiproliferative and causes G1 cell-cycle arrest associated with ERK activation and inhibition of p21 and p27 in the intestinal epithelial cells [263]. PKC δ is involved in proliferation defects affecting G1 and G2 phases [264], and is capable of downregulating the expression of cyclins causing cell-cycle arrest in lung adenocarcinoma cells [265, 266]. PKC/PKC α can also induce cell cycle withdrawal and growth suppression in intestinal epithelial cells, an event associated with rapid downregulation of cyclin D1 [267, 268], mediated by activation of 4E-BP1 and inhibition of cap-dependent translation initiation [269].…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…It has also been established that PKCs inhibit G1/S transition through the induction of the CDK inhibitor p21 via p53-independent mechanisms. PKC activation can also cause a delay in G2/M transition that results from the inhibition in the activity of Cdc2, a key G2/M regulator, and changes in Cdc25-B and C phosphatases that control Cdc2 dephosphorylation [159,160]. Studies in the last years established that PKCd mediates primarily anti-mitogenic and proapoptotic responses.…”
Section: Pkc Isozymes and Replicative Senescencementioning
confidence: 98%
“…Evidence accumulated in the last years revealed that these kinases regulate the cell cycle machinery both through translational and post-translational mechanisms, and distinct roles for individual PKC isozymes have been established in different phases of the cell cycle [159,160]. For example, the PKC activator phorbol 12-myristate 13-acetate (PMA or TPA) can inhibit G1/S progression in numerous cell types, an effect closely associated with the control of pRb phosphorylation and the expression of E2F-regulated genes.…”
Section: Pkc Isozymes and Replicative Senescencementioning
confidence: 99%